Where are they going, and what can we do to keep them? Intent to leave among nurses in British Columbia, Canada - Mycal Barrowclough; Tarya Morel; Shuyi Chua; Sandra Wu (York University Libraries, 2023)
Purpose. To identify: (1) alternate professions being considered by nurses, and (2) potential policy levers to retain them. Methods. This study describes responses to a subset of questions on a survey of nearly 15,000 nurses in British Columbia. Participants expressing intent to leave were asked what other professional options they were considering, and what changes they would need to keep them in nursing. We used thematic analysis to identify themes and sub-themes of participant responses. Results. Fewer than one in five nurses expressed intent to stay in the profession for more than two years. Participants cited a wide variety of other professional options available to them; the most commonly cited category was 'anything but nursing'. When asked what they needed to stay in nursing, participants described improvements in compensation, safe staffing, work/life balance, workplace culture, physical and psychological safety, and opportunities for advancement.